Examining the clinical learning environment through the architectural avenue. (3rd April 2019) - Nordquist, Jonas; Chan, Ming-Ka; Maniate, Jerry; Cook, David; Kelly, Cathal; McDougall, Allan
Abstract: Medical education has traditionally focused on the learners, the educators, and the curriculum, while tending to overlook the role of the designed environment. Experience indicates, however, that processes and outcomes of medical education are sensitive to the qualities and disposition of the spaces in which it occurs. This includes the clinical education within the patient care environment, termed the clinical learning environment (CLE). Recognition of this has informed the design of some new clinical learning spaces for the past decade. Competency-based clinical education can drive design requirements that differ materially from those associated with general purpose educational or clinical spaces. In this article, we outline two conceptual frameworks: (i) materialist spatiality and (ii) actor-network theory and consider how they can guide the design of spaces to support competency-based medical education and to guide the evaluation and discussion of the educational impacts of the spaces once built. We illustrate the use of these frameworks through discussion of the educational ambitions that underpinned the design of some recent clinical educational spaces. We close with practical points for consideration by educators and designers.